Mucosa-coring salvage (MU-CO-SAL) appendicectomy: A useful technique in the management of neglected appendicular mass - V Raveenthiran; R Abhinav Bharadwaj (Wolters Kluwer Medknow Publications, 2020)
In the presence of an appendicular mass, surgery is generally limited to the drainage of abscess. Scientific literature is sparse and controversial as to how the ongoing sepsis despite the drainage of appendicular abscess should be managed. Deliberate appendicectomy in the presence of mass formation is often not recommended as it may cause collateral damage to the adherent bowel loops. The authors describe a useful technique of doing appendicectomy by stripping the mucosa alone, leaving behind the adherent muscular cuff undisturbed. This technique is given an acronym "mucosa-coring salvage (MU-CO-SAL) appendicectomy." This article is intended to draw the attention of pediatric surgeons to this useful technique, which remains underutilized despite being described almost a decade ago.